PERILAKU STRUKTUR SISTEM LANTAI KAYU LVL SENGON - , DANI ASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Laminated timber is currently the most public-demanded construction material. One of the applications of laminated timber is for wooden flooring system at multi-story house. Wooden flooring system consists of beams assembled in parallel direction with particular distance and covered with wooden plank on the top of it. This research use Sengon LVL (Laminated Veneer Lumber) and plywood which are assembled into wooden flooring system. The beam used in this wooden flooring system is a box beam consisting of two LVL beams with dimension 40x60x2400 mm, both sides are connected using plywood with dimension 9x300x2400 mm. The length and width of the flooring system is 2400 mm and 500 mm. Two samples of wooden flooring system were used and different loadings were applied at each sample. The loading include line load and distributed load. The analysis of flexure stress and shear stress at the beam and the analysis of connection strength were conducted. This research resulted the value of maximum loading when the samples failed is 56,98 kN at line load and 62,97 at distributed load. The failure occurred during the test is failure at the connection with shear strength value of 51,5 kN. Load capacity at deflection of L/300 or 8 mm from line load is 19,26 kN/m2 and from distributed load is 18,75 kN/m2. The load capacity comply the requirements of load capacity in SNI Tata Cara Perencanaan Pembebanan untuk Rumah dan Gedung in residential house category 1,25 kN/m2. Keywords : LVL Sengon, plywood, floor system.